THE EFFECT OF USING WHATSAPP AS A SOCIAL MEDIA TO THE DISSEMINATION OF IMMIGRATION SERVICES INFORMATION AT IMMIGRATION OFFICE CLASS ONE SPECIAL OF NON BORDER CONTROL SOUTH JAKARTA - Annisa Nuril Ikhtiram (Polteknik Imigrasi, 2019)
The purpose of this research is to know the effectiveness of using WhatsApp as a social media in the dissemination of learning information at Immigration Office Class One Special of Non Border Control South Jakarta. This research used quantitative method, more the Associative Causal Relationship Method. The population of this research were all employe of Immigration Office Class One Special of Non Border Control South Jakarta with total population is 176 and the sample are 122 respondens. Research data was collected using a questionnaire and observation. The result of the research from the Hypotesis Test t is significance, the use of WhatsApp as a social media in the coefficients value table is 0,003 smaller than 0,05. The conclution is the use of WhatsApp as a social media gives effect in spreading the Immigration Services Information. The test results of Pearson Correlation Coefficient of the Correlation value is 0,363 which means the level of correlation between the two variables is stong. The result of Determination Coefficient Test, shows the amount of adjusted R square is 0,132, which means the use of WhatsApp as social media has an effect of 13,2% to the dissemination of Immigration Services Information. While the rest (100%-13,2% = 86,8%) is explained by other causes.